Práticas informacionais de travestis da Grande Vitória (ES) - Nascimento, Marcela Aguiar da Silva (2021)
All social action derives from the double movement between subjectivity and cultural conditioning to which the subjects are based. Studies on informational practices show how daily actions, interrelationships, intersectionality and socio-cultural contexts dynamize and interfere in the informational path. Research on informational practices of LGBTQIA+ subjects shows that there is a gap with regard to the specificities of the processes of searching, accessing, appropriating, using and sharing information from the transvestite community. As transvestites are simultaneously visible (through the media) and invisible (due to discrimination), it is a challenge to examine issues related to their engagement with information. Taking into account that informational subjects are not isolated in a private environment, that identities are built from interrelations and that informational phenomena are crossed by political, economic, symbolic and identity demarcations, the following question was raised: to what extent does gender identity influence aspects related to the search, access, appropriation, use and dissemination of information about transvestites in Grande Vitória (ES) in their daily lives? In this sense, it became essential to investigate the needs, sources, social / collective dispositions and informational negotiations of this population in an intersectional bias, covering categories such as gender, race / ethnicity and social class. Therefore, the general objective of this research is to analyze the informational practices of transvestites in Grande Vitória (ES) in the face of the process of construction of gender identity. From a methodological point of view, it is an exploratory research with a qualitative character. As a tool for data collection, semi-structured interviews were used, guided by a three-block script, with eight transvestites living in Grande Vitória (ES). The results showed that, since childhood, transvestites are related to femininity and that the domestic environment is part of the extension of cisgender and heterosexual values. The main information needs are consistent with the restructuring of the body through synthetic and contraceptive mechanisms. The information sources most used by transvestites feed on the continuous cycle of information exchange: transvestites search with other transvestites. The difference markers (gender, race / ethnicity, social class) symbolize a triple inference in the informational search. The use of information occurs with the objective of rebuilding citizenship and in the dissemination of information about performance, body, identity and femininity through their feminized corporealities. The context of transvestites is imbricated by intersections and social interactions that influence the entire process of informational practices.